Correlations between empathy fatigue, occupational identity, and sleep quality in nursing staff: a cross-sectional study - Zhao, Yingying; Wang, Xin; Liu, Tao (Frontiers in Public Health, 2024)
Abstract Objective: To investigate the status quo of empathic fatigue, professional identity and sleep quality of nursing staff in nursing institutions. To analyze the correlation between empathic fatigue, professional identity and sleep quality of nursing staff. Methods: This is a cross-sectional study. The method of convenient sampling was used to select 224 nursing workers from the elderly institutions in the Panjin area as the investigation objects. The nurses' general data questionnaire, the Chinese version of the compassion fatigue short scale, the nurses' professional identity Scale, and the Pittsburgh Sleep Quality Index were used as evaluation tools. SPSS26.0 statistical software was used to sort out and analyze the data. Results: There was a positive correlation between empathic fatigue and sleep quality; There was a negative correlation between empathy fatigue and professional identity. Occupational identity and sleep quality were negatively correlated. Conclusion: There is a correlation between empathic fatigue, professional identity, and sleep quality of nursing workers. Empathy fatigue is positively correlated with sleep quality. Empathy fatigue was negatively correlated with professional identity. Occupational identity was negatively correlated with sleep quality. To provide a theoretical basis for the management of elderly nursing staff and the formulation of corresponding management systems and policies, promote the mental health of elderly nursing staff, improve sleep quality, and provide a theoretical basis and reference for future intervention research.